Produksi Bioetanol Ratun Pertama Sorgum Manis Varietas Super-1 pada Perbedaan Jumlah Tunas dan Umur Panen Tanaman Primer - Da Rato, Yoseph Yakob; Syaiful, Syatrianty A; Riadi, Muhammad; Pabendon, Marcia B. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2019)
The research is aimed at discovering the influence of harvesting time of primary plant and buds number on the growth and production of Ratoon Super-1 Sweet Sorghum. The research was held at Cereal Crops Research Institute (Balitsereal) in Maros, South Sulawesi, from September 2017 to January 2018. It used ratoon plants from previous research that planted using super-1 sorghum variety seeds. This research was arranged based on split-plot-design with three replications. Main plot was numbers of ratoon buds (T) after harvesting the primary plants i.e : 1 (one) ratoon buds (T1), 2 (two) ratoon buds (T2), 3 (three) ratoon buds (T3), 4 (four) ratoon buds (T4) and 5 (five) ratoon buds (T5), while sub plot was harvesting time of primary plants i.e : 102 DAP (P1), 109 DAP (P2), 116 DAP (P3) and 123 DAP (P4). Every treatment combination repeated three (3) times to form 60 experimental plots. Interaction of ratoon with 3 buds and harvest of primary plant at 123 DAP reached the largest stem diameter (15,14 mm), the heaviest total biomass (28,43 tons/ha) and stem biomass (20,75 tons/ha), the highest juice volume (1274,33 L/ha) and the highest 90% ethanol content (415,00 L/ha).